Exploring the spatial distribution of interstitial cells in kidney tissue - Jingyun Ou; Huiyi Zeng; Yu Shangguan; Shaodong Luan; Hongwei Wu; Haitao Li; Wenyu Gong; Donge Tang; Xiaojun Tan; Lianghong Yin; Yong Dai (Karger Publishers, 2024)
Introduction: Interstitial cells are crucial to the development of kidney structure and function, although the mechanism underlying their role in it remains unclear to date. Our previous study identified cell clusters in human fetal kidney tissue, and we further analyzed the interstitial cell cluster within this context. Methods: We extracted the barcoded cDNA from tissue samples and prepared spatial transcriptome libraries. Sequencing data was quality-checked, normalized, and clusters were identified using Seurat. Single-cell and spatial data were integrated using MIA and cell types were deconvoluted. DEGs in interstitial cells were identified and functionally annotated using DAVID. CellPhoneDB was used to predict ligand-receptor interactions between cell types. Results: The results of the present study revealed that this cluster of interstitial cells appeared to be scattered in the junction between the cortical and medullary regions. The subsequent KEGG pathway analysis revealed that the differentially expressed genes (DEGs) in this cluster of interstitial cells were involved in the WNT signaling pathway. The Gene Ontology (GO) analysis revealed that these DEGs were involved in multiple pathways associated with kidney development, with six of the genes (NKD2, TCF21, WNT5A, WNT4, MDK, and SFRP1) associated with kidney development exhibiting significant upregulation. Accordingly, it was inferred that these interstitial cells might be involved in regulating epithelial cell differentiation, ureteral bud development, and morphogenesis. The subsequent cell-cell communication analysis revealed that the cellular crosstalk was primarily regulated mainly by ligand-receptor pairs. Additionally, 17 genes reported to be associated with kidney disease were focused on, and these genes were found to be predominantly expressed in a single cell type. Conclusion: In summary, the present study revealed the characteristics of a previously identified cluster of interstitial cells in the kidney tissue, thereby providing fresh insights into the process of kidney development.